2020
DOI: 10.2118/189787-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Entrained Hydrocarbon and Organic-Matter Components on Reservoir Quality of Organic-Rich Shales: Implications for “Sweet Spot” Identification and Enhanced-Oil-Recovery Applications in the Duvernay Formation (Canada)

Abstract: Summary The hydrocarbon (HC)-storage capacity of organic-rich shales depends on porosity and surface area, whereas pore-throat-size distribution and pore-throat-network connectivity control permeability. The pores within the organic matter (OM) of organic-rich shales develop during thermal maturation as different HC phases are generated and expelled from the OM. Organic-rich shales can potentially retain a large proportion of the HCs generated during the diagenesis process. Commercial HC product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…According to SAXS profiles the variations of the isolated kerogen porosity are mainly due to the decrease in the overall electronic contrast between pores and OM. This may indicate a loss of the primary OM porosity by kerogen deformations during oil generation, such as swelling of kerogen by retained oil as described by Mathia et al (2016) and recently observed by Ghanizadeh et al (2020). The filling of part of the total rock pore volume by the bitumen and oil trapped in the porosity (not extracted before nitrogen adsorption measurements) may explain a great part of the total pore volume loss, (Figure 14), however, the OM porosity (SAXS porosity, P) was measured after the extraction of bitumen and oil by dichloromethane/methanol treatments.…”
Section: Evolution Of the Ultrafine Structure Of Om During Oil And Gas Generationmentioning
confidence: 53%
“…According to SAXS profiles the variations of the isolated kerogen porosity are mainly due to the decrease in the overall electronic contrast between pores and OM. This may indicate a loss of the primary OM porosity by kerogen deformations during oil generation, such as swelling of kerogen by retained oil as described by Mathia et al (2016) and recently observed by Ghanizadeh et al (2020). The filling of part of the total rock pore volume by the bitumen and oil trapped in the porosity (not extracted before nitrogen adsorption measurements) may explain a great part of the total pore volume loss, (Figure 14), however, the OM porosity (SAXS porosity, P) was measured after the extraction of bitumen and oil by dichloromethane/methanol treatments.…”
Section: Evolution Of the Ultrafine Structure Of Om During Oil And Gas Generationmentioning
confidence: 53%
“…The effective diffusion/dispersion coefficients and the fracture aperture were selected as the primary input parameters for optimizing the experimental conditions because they were highly uncertain and the most impactful on oil production/recovery. Matrix permeability was also adjusted slightly but only within the range previously reported for other (Duvernay shale) twin core plug samples with similar porosity and organic/inorganic composition 31 . Two-phase (gas/liquid) relative permeability data, obtained for tight siliceous samples 29 from the Western Canadian Sedimentary Basin were also among the initial selected parameters to constrain the simulation.…”
Section: Numerical Simulation: Prior To Experimentsmentioning
confidence: 65%
“…These samples (1.5″ diameter, 2″ length) were drilled parallel to bedding from a 2/3 slabbed core obtained from a vertical well drilled into low-permeability intervals of the Duvernay Formation (Alberta, western Canada). A comprehensive series of geochemical, petrophysical and geomechanical analyses were previously performed on sample pieces and twin core plug samples obtained from the same well and depth 29,39 , serving as an important reference point for the current study. The analyzed samples have the following geochemical and petrophysical properties based on the sub-samples taken from the vicinity of these two core plugs: total organic carbon (TOC) content: 4.26 wt.%; clay content: 33.3%; quartz content: 44.7%; carbonate content: 12.4%; helium porosity: 2.1-3.3%; slip-corrected gas (N 2 ) permeability (1.25•10 -4 md; 900 psi effective stress).…”
Section: Samplesmentioning
confidence: 99%
“…Because it is challenging to collect shale sample from immature to overmature stages, the hydrocarbon generation, retention and expulsion evolution profiles of shales can be established through thermal simulation experiments (Ma et al, 2018). Thermal simulation systems can be divided into open, closed and semiclosed systems, and they produce different results (Ghanizadeh et al, 2020). Under geological conditions, petroleum generation, retention and expulsion follow a kinetic evolution process.…”
Section: Thermal Simulation Methodsmentioning
confidence: 99%
“…Compared to conventional petroleum systems, shale strata exhibit the characteristics of low porosity and ultralow permeability, and shale oil and gas have received insufficient attention for a long time due to the great difficulty of exploitation (Jarvie, 2012;Chen L. et al, 2019b;Soeder and Borglum, 2019). However, in recent years, with the progress of horizontal drilling, multistage hydraulic fracturing and other engineering techniques, shale oil and gas have become resources with an appreciable development potential (Wang et al, 2015a;Kumar et al, 2017;Zou et al, 2017;Zhao et al, 2018;Chen L. et al, 2019b;Ghanizadeh et al, 2020;Chen et al, 2021). The large-scale development of shale oil in the Permian Basin, Gulf Basin and Williston Basin has provided a new perspective for oil exploration and development (Bai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%